A contemporary guide to literary terms : with strategies for writing essays about literature - Barton, Edwin J.; Hudson, Glenda A. (Boston : Houghton Mifflin, 1997)
This book is about: Glossary; Strategies for writing essays about literature;...
Keywords: Literature; Terminology; Criticism; Literary form; English language -- Terms and phrases; Criticism -- Authorship; Criticism -- Terminology; Literature -- Terminology; Literary form -- Terminology